2021
DOI: 10.11604/pamj.2021.38.169.22405
|View full text |Cite
|
Sign up to set email alerts
|

Pleurodesis with povidone iodine in patients with malignant pleural effusion in a tertiary center in Nigeria

Abstract: Introduction malignant pleural effusion occurs as a consequence of a primary or metastatic malignant process involving the pleura. The aim of pleurodesis is to prevent re-accumulation of the effusion and avoid the need for repeated hospitalization. Povidone iodine has been used in other climes for pleurodesis with good results. The aim of this study is to assess the efficacy and safety of povidone iodine in producing pleurodesis as compared to tetracycline. Methods the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Omoregbee and Okugbo [40] found that iodopovidine was effective as tetracycline for pleurodesis in patients with MPE with an overall success rate of 93.4% and 93.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Omoregbee and Okugbo [40] found that iodopovidine was effective as tetracycline for pleurodesis in patients with MPE with an overall success rate of 93.4% and 93.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The use of povidone-iodine in inducing apoptosis has largely been described in, in vitro studies, however povidone-iodine has also been described as a safe alternative in chemical pleurodesis in the context of malignant pleural effusions, with results comparable to cisplatin ( 12 ), gemcitabine ( 14 ), bleomycin ( 19 , 20 ), tetracycline ( 21 ), and talc ( 22 , 23 ). In vitro studies have shown povidone-iodine to have no effect on apoptosis proteins expressed on MPM cells, however it inhibits cell growth ( 6 ), and exhibits a necrotic rather than apoptotic mechanism of cell death ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference. [9][10][11][12] One of the successes of pleurodesis is determined by the type of sclerosant 3224 used. Various substances have been reported to have been used as pleurodesis agents, including talc, oxytetracycline, quinacrine, bleomycin, mitomycin, and povidone-iodine.…”
Section: Discussionmentioning
confidence: 99%